Magnet magic - Adams, Phyllis (Cleveland, Ohio : Modern Curriculum, 1987)
When two children go to the hardware store to buy some nails, the storekeeper shows them some things one can do with a magnet.
Keywords: Magnets -- Fiction; Afro-American -- Fiction